Does delayed treatment affect the survival of patients with hepatocellular carcinoma? - Liao, Ying-Yang; Ou, Jie; Luo, Cheng-Piao; Peng, Ning-Fu; Zhong, Jian-Hong (Translational Cancer Research, 2018)
Hepatocellular carcinoma (HCC) progresses at highly variable rates. It is widely believed that active treatment should begin as soon as possible after diagnosis. This may not always occur for various reasons, and it remains unclear whether such delays shorten overall survival.